Efektivitas Penerapan Full Day School di Sekolah Menengah - Miftah Afifah Zafar; Armida S (Jurnal Ecogen, 2020)
The literature review result article aims to determine the application of full day school in secondary schools. In this study the authors used a type of libary research with philosophical and pedagogical approaches. The results of the literature review found, the authors found that the application of full day school in secondary schools had reached a high or very effective level of qualification of 92% with the achievement of learning objective namely an increase in academic achievement of 87,5% and the formation of student characters reaching 92% in implementing this full day school. While the integrity in the implementation of full day school hs been running optimally and received a good response from parents of students as well as students and teacher and educators involved in implementing full day school. Furthermore, the adaptation of the application of full day school to the field conditions has reached 80% effective level with the maximum running of intracuricular activities, extracuricular activities, and religious activities, buth the curricular activities in implementing full day school have not reached good implementation.Keywords : effectiveness, full day school, secondary school.